Sequence stratigraphic investigation of the Early Miocene Formations in the Zagros Folded belt using wireline well logs analysis - Hussein, Devan Othman (Sulaimani Journal for Pure and Applied Sciences, 2020)
Based on the available core sample description and wireline log analysis, sedimentary facies, microfacies and lithofacies interpretation are evaluated to determine the large scale architecture in the Early Miocene formations, from close to the contemporaneous Lower Miocene depositional margin of the Zagros basin, as represented in outcrop sections, to productive oil field within the Kirkuk embayment equivalents ca. 100 km to the south-west and west. Sequence stratigraphic methods of sedimentary log interpretation and log correlation are used to construct a model of the overall regressive and transgressive or combined transgressive to regressive character of each of the formations, thus providing an indication of the gross reservoir stacking patterns over this distance. Based on outcrop descriptions and wireline log data the Dhiban Formation is interpreted as a lowstand system tract (LST) of a third order depositional sequence, lying between the Euphrates Formation regressive parasequence set that could represent a highstand systems tract (HST) of a third order sequence and the transgressive parasequence set (third order transgressive systems tract, TST) of the lower part of the Jeribe Formation. Several higher order transgressive and regressive cycles are evident within the Dhiban Formation in the subsurface sections. The transgressive cycles within the Dhiban formation are associated with the carbonate layers. Yellowish grey, friable anhydrite is recognized in the Dhiban Formation at outcrop, and thick anhydrite of low gamma ray and high density readings was identified in the subsurface sections. This lowstand evaporite system filling the basin centre can be confirmed as the relevant model for the mixed carbonate-evaporite basin at the scale of a third order cycle.
Keywords: Wierline well log; Sequence stratigraphy; Gamma Ray; Carbonate-Evaporite; Reservoir quality